Promiscuous and Adaptable Enzymes Fill “Holes” in the Tetrahydrofolate Pathway in Chlamydia Species - Nancy E. Adams (American Society for Microbiology, 2014)
ABSTRACT Folates are tripartite molecules comprising pterin, para-aminobenzoate (PABA), and glutamate moieties, which are essential cofactors involved in DNA and amino acid synthesis. The obligately intracellular Chlamydia species have lost several biosynthetic pathways for essential nutrients which they can obtain from their host but have retained the capacity to synthesize folate. In most bacteria, synthesis of the pterin moiety of folate requires the FolEQBK enzymes, while synthesis of the PABA moiety is carried out by the PabABC enzymes. Bioinformatic analyses reveal that while members of Chlamydia are missing the genes for FolE (GTP cyclohydrolase) and FolQ, which catalyze the initial steps in de novo synthesis of the pterin moiety, they have genes for the rest of the pterin pathway. We screened a chlamydial genomic library in deletion mutants of Escherichia coli to identify the “missing genes” and identified a novel enzyme, TrpFCtL2, which has broad substrate specificity. TrpFCtL2, in combination with GTP cyclohydrolase II (RibA), the first enzyme of riboflavin synthesis, provides a bypass of the first two canonical steps in folate synthesis catalyzed by FolE and FolQ. Notably, TrpFCtL2 retains the phosphoribosyl anthranilate isomerase activity of the original annotation. Additionally, we independently confirmed the recent discovery of a novel enzyme, CT610, which uses an unknown precursor to synthesize PABA and complements E. coli mutants with deletions of pabA, pabB, or pabC. Thus, Chlamydia species have evolved a variant folate synthesis pathway that employs a patchwork of promiscuous and adaptable enzymes recruited from other biosynthetic pathways. IMPORTANCE Collectively, the involvement of TrpFCtL2 and CT610 in the tetrahydrofolate pathway completes our understanding of folate biosynthesis in Chlamydia. Moreover, the novel roles for TrpFCtL2 and CT610 in the tetrahydrofolate pathway are sophisticated examples of how enzyme evolution plays a vital role in the adaptation of obligately intracellular organisms to host-specific niches. Enzymes like TrpFCtL2 which possess an enzyme fold common to many other enzymes are highly versatile and possess the capacity to evolve to catalyze related reactions in two different metabolic pathways. The continued identification of unique enzymes such as these in bacterial pathogens is important for development of antimicrobial compounds, as drugs that inhibit such enzymes would likely not have any targets in the host or the host’s normal microbial flora.